Knowledge and perception about family planning among women in selected rural communities of Ibadan (2012)
Family planning has become a major strategy of population control both at the national and global level. Yet, population growth in Nigeria remains high especially in rural areas due partly to lack of adequate knowledge and poor perception about the need to utilize family planning methods, the study seeks to . examine the knowledge and perception of women from selected rural areas in Ibadan about family planning. The Health Belief Model and Social Action Theory guided the explanation of the understudied phenomena. The study adopted a qualitative and quantitative approach which included a survey of 136 randomly selected mothers from 5 rural communities in Ibadan, 15 IDT, 5 Klls and 5 FGDs. The Statistical Package for Social Sciences was utilized in analyzing the quantitative data, while the qualitative data were analyzed using content analysis. Findings revealed that although the sources of awareness were many, very few women had adequate knowledge about family planning methods. The study also revealed that women perceived family planning as a welcomed strategy to control population and make mothers healthy and strong after child birth, however, fear of pushing their husbands outside and increased promiscuity as well as the perceived negative side effect such as stomach aches, bodily complications, menstrual maladjustment,. infertility, were the major barriers that affected women's expected behavioral changes towards family planning in the study areas. Also, family planning was also perceived as a woman's thing which makes men feel uncomfortable with it and' hardly encourage their wives to practice. Most women preferred . condom use and abstinence in planning their family only when their husbands suggested or approved. The study recommends family planning methods be taught both in orthodox and traditional health centres. It also recommends that women are adequately educated to participate significantly in decisions regarding family planning especially in the rural part of Nigeria. It was also recommended that family planning programmes be intensified to incorporate the male folk and improve people's knowledge and perception on the benefits of contraceptive use in order to achieve the desired behavioral change towards family planning in rural areas.